Panelling without walls: Narrating the border in Barrier. Issue 2 (1st November 2020) - Pinti, Daniel
Brian K. Vaughan's and Marcos Martin's science fiction comics series, Barrier (2015‐18), is a five-issue story set on the US-Mexican border and contributing to the continuing public discourse surrounding undocumented immigration in the United States. First appearing as a webcomic on Vaughan's Panel Syndicate website and later published in comic book form by Image Comics, Barrier's story of two characters, a Honduran refugee and a Texas rancher who struggle with and eventually come to rely on one another, depicts linguistic and cultural boundaries and borders, as well as the frustration and hostility they can generate. As comics, Barrier's very medium works by means of crossing boundaries and borders: binaries (like word and image) are complicated if not subverted, and the borders of each panel remain closed yet open for sequential art to function as a medium for narrative. Moreover, as a bilingual webcomic crossing into print yet all but encouraging an ongoing virtual engagement through web searches and Google Translate, the series demands further creative energy from the reader in reimaging various barriers, borders and positions of liminality. Although stories that represent various kinds of borders (social, cultural and geopolitical) and various ways of establishing, challenging, crossing or deconstructing borders are frequently found in graphic narratives, Barrier demonstrates the south-west border to be one the medium of comics is especially suited to explore. Barrier is a work that takes as its very subject, to borrow a phrase from Ramzi Fawaz, 'spatially drawn analogies' in order to engage graphically matters of genuine political import. In doing so, Barrier not only reflects obliquely on its own form, but also engages creatively with one of the most politically and culturally contested spaces in contemporary US culture.